PENGEMBANGAN KEWIRAUSAHAAN DI PESANTREN: ANTARA URGENSI DAN POTENSI (TELAAH ATAS HASIL PENELITIAN TENTANG KEWIRAUSAHAAN PADA TIGA PESANTREN: PESANTREN AINURRAFIQ KUNINGAN, PESANTREN WALINDO PEKALONGAN, DAN PESANTREN MIFTAHUL ULUM MADURA) - Haryanti, Sri; Dhofir, M. Alfan Haidar (Reflektika, 2022)
This study aims to describe the development of entrepreneurship in three Islamic boarding schools, namely: Ainurrafiq Islamic Boarding School, Kuningan, Walindo Islamic Boarding School, Pekalongan, and Miftahul Ulum Islamic Boarding School, Madura. The method used is content analysis carried out by deductively analyzing the three main sources of research results in the three pesantren by three previous researchers. The results of the study reveals that the three pesantren have relatively developed entrepreneurship, but are still in the early stages. Entrepreneurship is carried out based on local wisdom and only meets the internal needs and the surrounding community. From the case of entrepreneurship in the three pesantren, strong support from government policies towards entrepreneurship development is needed in the form of financial support, legislation, and also coaching. This needs to be done so that Islamic boarding schools become one of the driving forces for the growth of national entrepreneurship which ratio to the total population is only 3.3 percent.